Exploring ‘New Worlds’ through New Media in ELT classrooms (Journal of NELTA, 2018)
This article is based primarily on a shared virtual classroom of Macedonia, Europe and Nepal, Asia, and secondarily on a talk presented in Nepal English Language Teachers’ Association 19th International Conference 2014 held in Kathmandu, Nepal. It discusses how instructors and students had applied “New Media” in ELT classrooms with the aim of enhancing students’ English Language skills including 21st century literacies through a virtual cultural exchange session between Macedonian and Nepali classrooms. In other words, it explores how learning process can be optimized by using internet, computer, multimedia and mobile. Moreover, these tools can become a means to explore “New World(s)” which exists beyond one’s physical classroom.Journal of NELTA ,  Vol. 22, No. 1-2, 2017 December, Page: 103-109